Democracy, security and development in India - Thomas, Raju G. C (London, 1996)
Increasing pressures on Indian democracy have cast doubt on its ability to survive. Movements to separate from India include the Sikh attempts to establish Kalistan and the Nagaland tribesmen's fight for autonomy. These, along with the rapid polarization of Hindu and Muslim communities, have made governing India increasingly difficult. Written by an expert in the field, this book reveals the dilemmas facing a state committed both to achieving true pluralism and democracy and to maintaining law and order within its borders. Thomas argues that while human rights abuses in Kashmir certainly stem from authoritarian tendencies within the government and army, they also stem from a paralyzing fear of what would happen in the event of the dissolution of the Indian state into its hundreds of constituent parts.
Keywords: Economic development